PENINGKATAN KAPASITAS PENANGANAN KEGAWATDARURATAN DENGAN KASUS PATAH TULANG (FRAKTUR) PADA REMAJA - Ildsa Maulidya Mar'athus Nasokha; Asih Puji Utami; Ari Anggraeni; Hafidzoh Q. Fadhila; Aprillia Triwahyuningsih; Shelvira Salsabila; Anshor Nugroho (Yayasan Wayan Marwan Pulungan, 2023)
One of the most common consequences of a traffic accident is a femur fracture. Those fractures can cause bleeding, internal organ injury, wound infection, respiratory syndrome and disability. Several studies state that the age range of 16-20 years old has the most traffic accidents and fractures. A fracture is a disturbance of the normal continuity of a bone, if a fracture occurs, the surrounding soft tissue is also often disturbed. Radiographs (s-rays) can show bone injuries but are unable to show torn muscles or ligaments, severed nerves, or broken blood vessels which can complicate the client’s recovery. An open fracture is a condition where fragments are or have been in contact with the outside world (Black and Hawks, 2014). Inspection for a fracture by looking for swelling, visible bone protruding from soft tissue. Treatment in general in this emergency situation, one which is to immobilize the fracture with support, bandage or splint. Efforts to improve students’ skills in handling